Harmoni dalam Keberagaman: Toleransi dan Kerukunan Antar Umat Beragama Berdasarkan Al-Qur’an dan Hadits - Sukandarman Sukandarman; Ainur Rofiq Sofa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Religious tolerance and harmony are key elements in creating harmony in a diverse society, such as in Indonesia, where various religions and cultures coexist. In the perspective of the Qur'an and Hadith, tolerance is an important foundation that provides direction for mutual respect and appreciation of differences. This journal examines the importance of applying the values of tolerance in daily life and its implications for more harmonious social relationships. Special focus was given to SMPN 2 Sumberasih, a school with a majority of Muslim students and a small number of non-Muslim students. Through teaching and instilling the values of religious tolerance from an early age, this school plays a role in shaping students who are more peaceful, respectful, and harmonious. The results of this research are expected to be a positive contribution in developing a more tolerant generation in the future., this research provides insight into the importance of religious harmony values education in schools as one of the efforts to build social cohesion in a multicultural environment.